Pengaruh Konten Viral #BoikotAice Di Media Sosial Twitter Terhadap Citra Perusahaan PT. Alpen Food Industry Pada Masyarakat Pinang Sebatang Timur Perawang (Journal of Social Science and Digital Marketing, 2023)
The purpose of this study was to determine whether there is an effect of #BoikotAice viral content on Twitter social media on the corporate image of PT. Alpen Food Industry. The theory used is the stimulus-response (S-R) theory. The method used in this study is a quantitative method with an explanatory format. In the analysis of quantitative research methods using inferential statistical analysis. Researchers collected data using a questionnaire distributed in the village of Pinang Sebatang Timur RT004/RW006 Perawang to 60 respondents and the technique for determining the sample was using the purposive proportional random sampling technique with sampling using the Roescoe formula. To determine how much influence these two variables have, the researcher uses simple linear regression analysis. Processing of questionnaire test data using SPSS version 20. The results showed that the #Boikotaice Viral Content on Twitter social media had an influence on the corporate image of PT. Alpen Food Industry in Desa Pinang Sebatang Timur RT004/RW006 Perawang. The influence of the viral content of #BoikotAice on Twitter social media on the corporate image of PT. Alpen Food Industry is 24.6%, and 75.4% is influenced by other variables outside of this study.